Pembuatan Pupuk Kompos Dari Limbah Kulit Kopi Di Daerah Penghasil Kopi Nagari Koto Tuo, Sumatera Barat - Riga Riga; Trisna Kumala Sari; Dina Agustina; Bali Yana Fitri; Muhammad Habibul Ikhsan; Ferdi Henfi Pratama; Wandi Oktria (Universitas Mathla'ul Anwar Banten, 2022)
MAKİNG COMPOST FERTİLİZER FROM COFFEE PEEL WASTE İN THE NAGARİ KOTO TUO COFFEE-PRODUCİNG AREA, WEST SUMATRA. Coffee husk waste in the Nagari Koto Tuo coffee producing area is not used optimally. It just became a pile of garbage in several places. The others were burned which can cause health problems in the future. One alternative to manage coffee husk waste is to fermentate it into compost. The community service for the bioconversion of coffee husk waste into fertilizer is carried out in three steps. The aim of this activity is to increase the knowledge and skills of the community in utilizing coffee skin waste. The practice of making compost was carried out in a composter using the EM-4 bioactivator. The achievement obtained from this community service was that participants were able to understand the bioconversion process of coffee skin waste into compost, which was proven by the percentage of knowledge and skills (greater than 80%).